(untitled) (Quantum Journal of Engineering, Science and Technology, 2021)
The study area landscape is located in the semi desert zone north of Khartoum State, Khartoum Refinery (KRC) is located north of Khartoum State, Sudan; the objective of the research to investigate the tolerance plants for treated waste water at Khartoum Refinery Inaddtion to study phytoremedation of elements in Khartoum Refinery .The determination of elements was the atomic absorption. The study area was divided into control site (merely received rain water) and treated one (received rainwater and treated water). In KR, the treated area was subdivided into four units planted with Eucalyptus camaldulensis (Ban) based on age of plantation (6, 4, 2 years and 2 weeks). The results showed that plants Ca, Na, Mg concentrations in Khartoum Refinery was high and that plants Ca, Na, Mg concentrations in plantations of was Khartoum Refinery significantly different from control. The results showed that plants K, Zn, Fe, Cu and Mn concentrations in Khartoum Refinery was low, while Cr, Co, Cd and Pb were not detected.